Luteinizing Hormone and Testosterone Levels during Acute Phase of Severe Traumatic Brain Injury: Prognostic Implications for Adult Male Patients - Hohl, Alexandre; Zanela, Fernando Areas; Ghisi, Gabriela; Ronsoni, Marcelo Fernando; Diaz, Alexandre Paim; Schwarzbold, Marcelo Liborio; Dafre, Alcir Luiz; Reddi, Benjamin; Lin, Kátia; Pizzol, Felipe Dal; Walz, Roger (Frontiers in Endocrinology, 2018)
Traumatic brain injury (TBI) is a worldwide core public health problem affecting mostly young male subjects. An alarming increase in incidence has turned TBI into a leading cause of morbidity and mortality in young adults as well as a tremendous resource burden on the health and welfare sector. Hormone dysfunction is highly prevalent during the acute phase of severe TBI. In particular, investigation of the luteinizing hormone (LH) and testosterone levels during the acute phase of severe TBI in male has identified a high incidence of low testosterone levels in male patients (36.5% to 100%) but the prognostic significance of which remains controversial. Two independent studies showed that normal or elevated levels of LH levels earlier during hospitalization are significantly associated with higher mortality/morbidity. The association between LH and prognosis was independent of other predictive variables such as neuroimaging, admission Glasgow coma scale and pupillary reaction. The possible mechanisms underlying this association and further research directions in this field are discussed. Overall, current data suggest that LH levels during the acute phase of TBI might contribute to accurate prognostication and further prospective multicentric studies are required to develop more sophisticated predictive models incorporating biomarkers such as LH in the quest for accurate outcome prediction following TBI. Moreover, the potential therapeutic benefits of modulating LH during the acute phase of TBI warrant investigation.